A Numerical Investigation on the Structural Behavior of Deficient Steel Frames Strengthened using CFRP Composite - Amir Hamzah Keykha (Institute of Research and Community Outreach - Petra Christian University, 2018)
Carbon fiber reinforced polymers (CFRP) is one of the materials that is used to strengthen steel structures. Most studies on CFRP strengthening steel on structures have been done on beams and steel columns. No independent study has studied the effect of CFRP strengthening on the structural behavior of steel frames having initial deficiency.The deficiency in steel structures may be created due to the errors caused by construction and others.This study aims to carry out a numerical study on the efficiency of CFRP sheet on strengthening square hollow section (SHS) steel frames having initial deficiency. Seven specimens, five of which were strengthened using CFRP sheets, were analyzed. ANSYS software was used to analyze the SHS steel frames. The results showed that the coverage length, the width, and the number of CFRP layers have a significant effect on increasing and recovering the ultimate load capacity of the SHS steel frames having initial deficiency.